Risk Reduction of Alzheimer’s Disease by Coffee and Caffeine - Potikanond, Saranyapin; Sangdee, Chaichan (Journal of Basic and Applied Pharmacology, 2015)
Alzheimer’s disease, a neurodegenerative disease, usually attack susceptible elderly individuals and it accounts for the majority of people with dementia. At present, although drugs for the treatment of Alzheimer’s disease are available, but they are low in efficacy, their usefulness lasts only for 3-5 years. These drugs offer only symptomatic treatment and cannot even slow the disease progression. For the last 2 decades, epidemiological studies indicate that coffee and caffeine consumption can slow down the cognitive decline and dementia and reduce the risk of Alzheimer’s disease. Recently, case-control and cohort studies and meta-analysis support and extend the results of earlier studies that coffee and caffeine can prevent or reduce the risk of dementia and Alzheimer’s disease in humans. Surprisingly, caffeine consumption has been found to be more efficacious to reduce cognitive decline and lower the risk of Alzheimer’s disease in women than in men. The active substance in coffee to exert protective effects on cognition, dementia and Alzheimer’s disease is caffeine and supportive evidence derives from studies of direct effect of caffeine in several animal models of Alzheimer’s disease. It is well accepted that caffeine acts as adenosine A1 and A2A receptors antagonist in the brain. In the brain of patients with Alzheimer’s disease, certain elderly, and insults to the brain including ischemia, neuro-inflammation, and amyloid β deposition, all lead to over expression of A2A receptors and increased adenosine levels. Abnormally high levels of adenosine in these settings in turn overly activates A2A receptors that results in increased levels of glutamate, pro-inflammatory factors, and amyloid β that finally cause brain damage and is implicated in the basis of pathogenesis of dementia and Alzheimer’s disease. Caffeine, by blocking the over expression of A2A receptors, therefore renders its protective effects against dementia and Alzheimer’s disease. In addition to A2A receptors antagonism, caffeine has been found to protect against blood-barrier disruption and to increase excretion of brain amyloid β by increasing cerebrospinal fluid synthesis and to increase expression of P-glycoprotein in the endothelial membrane of brain blood vessels. From the above mentioned beneficial effects of caffeine lead to the phase 2-3 clinical trial of newly developed selective A2A receptor antagonist for the treatment dementia and Alzheimer’s disease.